Impact of Seminal Plasma Antioxidants on DNA Fragmentation and Lipid Peroxidation of Frozen-Thawed Horse Sperm - Jaime Catalán; Iván Yánez-Ortiz; Marc Torres-Garrido; Jordi Ribas-Maynou; Marc Llavanera; Isabel Barranco; Marc Yeste; Jordi Miró (MDPI AG, 2024)
Cryopreservation is a stressful process for sperm, as it is associated with an increased production of reactive oxygen species (ROS). Elevated ROS levels, which create an imbalance with antioxidant capacity, may result in membrane lipid peroxidation (LPO), protein damage and DNA fragmentation. This study aimed to determine whether the membrane LPO and DNA fragmentation of frozen-thawed horse sperm relies upon antioxidant activity, including enzymes (superoxide dismutase (SOD), glutathione peroxidase (GPX), catalase (CAT) and paraoxonase type 1 (PON1)); non-enzymatic antioxidant capacity (Trolox-equivalent antioxidant capacity (TEAC), plasma ferric reducing antioxidant capacity (FRAP) and cupric reducing antioxidant capacity (CUPRAC)); and the oxidative stress index (OSI) of their seminal plasma (SP). Based on total motility and plasma membrane integrity (SYBR14+/PI−) after thawing, ejaculates were hierarchically (p < 0.001) clustered into two groups of good- (GFEs) and poor-(PFEs) freezability ejaculates. LPO and DNA fragmentation (global DNA breaks) were higher (p < 0.05) in the PFE group than in the GFE group, with LPO and DNA fragmentation (global DNA breaks) after thawing showing a positive relationship (p < 0.05) with SP OSI levels and ROS production. In addition, sperm motility and membrane integrity after thawing were negatively (p < 0.05) correlated with the activity levels of SP antioxidants (PON1 and TEAC). The present results indicate that LPO and DNA fragmentation in frozen-thawed horse sperm vary between ejaculates. These differences could result from variations in the activity of antioxidants (PON1 and TEAC) and the balance between the oxidant and antioxidant components present in the SP.